IMPLEMENTASI KEBIJAKAN PAJAK REKLAME PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KABUPATEN MINAHASA - TOLOLIU, ANDRE WILDY; OGOTAN, MARTHA; LONDA, VERY (Sam Ratulangi University, 2018)
The research objective was determine the implementation of advertisement tax policy in the taxand retribution management body in the Minahasa district. This study uses qualitative approach ofinformants in this study as many as 5 people, namely the head of the agency, the head of the datacollection field, an executor, and an advertisement taxpayer. Data collection uses interview andobservation guidelines; while the analytical technique used is an interactive analysis model from Milesand Hubernann. Based on the results of the data analysis, it was concluded that the implementation of theadvertisement tax policy in the tax and retribution management body in the Minahasa regency viewedfrom the dimensions of the idealized policy, the target groups dimensions, the implementing organizationdimension, and the dimensions of environmental factors, were not optimal. Based on the conclusions theresults of the study are recommended: (1) the dimensions of the â€œidealized policyâ€ need to be improved bybuilding more effective communication with the subjects of advertisement tax, as well as increasingcoordination with relevant parties; (2) The dimensions of â€œtarget groupsâ€ needs to be increased by takingnore effective actions to increase the awareness of the subject of tax compliance with their tax obligations;(3) The dimensions of â€œImplementing organizationâ€ needs to be improved by optimizing theimplementation of the duties and fuctions of the unit/unit of the organization responsible for managingadvertisement tax; (4) the dimensions of â€œenvironmental factorsâ€ needs to be improved by seeking tocreate more conducive social and cultural conditions.Keywords : Policy Implementation, Advertisement Tax